Effects of Piper betle Extracts against Biofilm Formation by Methicillin-Resistant Staphylococcus pseudintermedius Isolated from Dogs - Arpron Leesombun; Sivapong Sungpradit; Norasuthi Bangphoomi; Orathai Thongjuy; Jantraporn Wechusdorn; Sunee Riengvirodkij; Jakaphan Wannawong; Sookruetai Boonmasawai (MDPI AG, 2023)
Emergence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) isolated from dogs with cutaneous and wound infections has significantly impacted veterinary medicine. This study aimed to isolate S. pseudintermedius from canine pyoderma and investigate the effects of ethanolic extracts of Piper betle (PB), P. sarmentosum (PS), and P. nigrum (PN) on the bacterial growth and biofilm formation of S. pseudintermedius and MRSP. Of the isolated 152 isolates, 53 were identified as S. pseudintermedius using polymerase chain reaction, and 10 isolates (6.58%) were identified as MRSP based on the presence of mecA. Based on phenotype, 90% of MRSPs were multidrug-resistant. All MRSP had moderate (10%, 1/10) and strong (90%, 9/10) biofilm production ability. PB extracts were the most effective in inhibiting planktonic cells, and the minimum inhibitory concentration at which ≥50% of the isolates were inhibited (MIC50) was 256 µg/mL (256-1024 µg/mL) for S. pseudintermedius isolates and 512 µg/mL (256-1024 µg/mL) for MRSP isolates. The MIC90 for S. pseudintermedius and MRSP was 512 µg/mL. In XTT assay, PB at 4× MIC showed an inhibition rate of 39.66-68.90% and 45.58-59.13% for S. pseudintermedius and MRSP, respectively, in inhibiting biofilm formation. For PB at 8× MIC, the inhibition rates for S. pseudintermedius and MRSP were 50.74-81.66% and 59.57-78.33%, respectively. Further, 18 compounds were identified in PB using gas chromatography-mass spectrometry, and hydroxychavicol (36.02%) was the major constituent. These results indicated that PB could inhibit bacteria growth of and biofilm formation by S. pseudintermedius and MRSP isolated from canine pyoderma in a concentration-dependent manner. Therefore, PB is a potential candidate for the treatment of MRSP infection and biofilm formation in veterinary medicine.